Pengaruh Penggunaan Metode Tartilqu terhadap Kemampuan Membaca Al-Qur’an Anak TPA - Sutiah; Zulhijra; Irja Putra Pratama (PAI RAFAH, 2025)
Of the 225 million Muslim population in Indonesia, about 54% are categorised as not knowing the Qur'an, so about 46% know the letters and can recite the Qur'an. This study aims to analyse the use of the Tartilqu method on the ability to read the Qur'an of children of TPA Rabbani Palembang. The sample used in the study was TPA Rabbani students with a total of 20 students selected from a population of 20 students. The research data were collected by observation, oral tests and documentation. The collected data were then analysed using descriptive analysis and inferential analysis. The results showed that there was a significant effect of the use of the Tartilqu method on the ability to read the Qur'an of the students. Based on the results of the analysis output of IBM SPSS version 30, that (Sig. 2 tailed) of 0.001 <0.05 then H0 is rejected and Ha is accepted, meaning that in the comparison of t count with t table, t count is greater in value than t table while the value (P-Value) is smaller than the value of 0.05 then there is a significant influence on the ability to read the Qur'an using the Tartilqu method.